Protein particle vaccines against malaria. - Gilbert, S; Hill, A (1997)
Many viral coat proteins retain the ability to assemble into virus-like particles when produced as recombinant proteins. These small particles are highly immunogenic, and in many cases can be used to carry epitopes or antigens from other pathogens. Most particle-forming proteins can tolerate only small additions or alterations to their sequence, but Hepatitis B virus surface antigen (HBsAg) and the yeast-derived Ty particle are exceptionel in their ability to form particles with long N- or C-terminal extensions. Both have been used to produce hybrid particles carrying Plasmodium sequences. These have been shown to be highly immunogenic in animal studies and also in human phase I trials, in the case of HBsAg. Recently, six out of seven human volunteers were protected against sporozoite challenge by a recombinant HBsAg particle vaccine, the most encouraging result to date for any pre-erythrocytic malaria vaccine. Here, Sarah Gilbert and Adrian Hill review the prospects for the future development of protein particle vaccines against malaria.